Understanding Innovation in Small Firms: A Systematic Literature Review of Heterogeneity in Definitions, Drivers, and Measurement - Chowdhury, Subarna Roy; Saha, Debdatta (West Science Journal Economic and Entrepreneurship, 2026)
Innovation in small firms is widely recognized as a critical driver of economic growth and competitiveness, yet its conceptualization and measurement remain highly fragmented. This paper addresses this gap by conducting a systematic literature review of 367 studies on innovation in small firms across diverse geographical and institutional contexts. Drawing on the resource-based view and institutional theory, the study examines how small firms are defined, how their innovation activities are characterized, and how such activities are measured in the existing literature. The findings reveal substantial heterogeneity in the definition of small firms, with significant variation across countries, datasets, and registration status. The analysis further shows that innovation in small firms is predominantly incremental, necessity-driven, and often takes the form of frugal and informal practices, particularly in resource-constrained environments. However, widely used indicators such as patents and R&D expenditure largely capture formal innovation and therefore systematically underestimate the innovative activities of small firms. The paper identifies a critical measurement gap between actual innovation practices and their empirical representation. By highlighting this misalignment, the study contributes to the literature by demonstrating the limitations of conventional innovation metrics and emphasizing the need for more inclusive and context-sensitive measurement frameworks. The findings have important implications for both researchers and policymakers, suggesting that current approaches may overlook a significant portion of innovation activity in small firms, particularly in emerging economies.
Keywords: Systematic Literature Review; Innovation; Small Firms; Heterogeneity; Definitions; Drivers; Measurement